ChemInform Abstract: Alternative Fuel Additives from Glycerol by Etherification with Isobutene: Structure‐Performance Relationships in Solid Catalysts. Issue 7 (January 2016) - Bozkurt, Ozge D.; Tunc, F. Meliz; Baglar, Nur; Celebi, Serdar; Gunbas, I. Dogan; Uzun, Alper
Abstract: Review: 154 refs.